The social economy of France - Coffey, Peter (New York : St. Martin's Press, 1973)
Fifty years after Algerian independence, the legacy of France's Algerian past, and the ongoing complexities of the Franco-Algerian relationship, remain a key preoccupation in both countries. A central role in shaping understanding of their shared past and present is played by visual culture. This study investigates how relations between France and Algeria have been represented and contested through visual means since the outbreak of the Algerian War in 1954. It probes the contours of colonial and postcolonial visual culture in both countries, highlighting the important roles played by still and moving images when Franco-Algerian relations are imagined. Analysing a wide range of images made on both sides of the Mediterranean--from colonial picture postcards of French Algeria to contemporary representations of postcolonial Algiers--this new book is the first to trace the circulation of, and connections between, a diverse range of images and media within this field of visual culture. It shows how the visual representation of Franco-Algerian links informs our understanding both of the lived experience of postcoloniality within Europe and the Maghreb, and of wider contemporary geopolitics.
Includes bibliographical references.
aia 26/9/2018
Loan
Keywords: France; France